A review of Nigerian energy access studies: The story told so far. (March 2020) - Ugwoke, B.; Gershon, O.; Becchio, C.; Corgnati, S.P.; Leone, P.
Abstract: Nigeria has been accorded the largest economy in Africa and one of Africa's burgeoning economies. However, a high percentage of the population lives in extreme poverty and is largely rural, accounting for about 51% of the total, approximately 96 million people in 2016. This glaring reality is most evident in the undisputed urban and rural divide with a huge mass of the population living in these rural areas characterised by underdevelopment and limited access to electricity and modern energy services. Energy access is an indispensable instrument such that can be used to achieve great strides in human development, better the economy and enable sustainable development. The present work reviews the state of the art on Nigerian energy access studies and provides an overview of the peer-reviewed literature spanning energy planning, electrification planning, rural electrification, renewable resource potential, energy & electricity access impact, and policies & reforms. It delineates the narrative in existing literature and propounds a new trajectory for future work. This study was facilitated by an extensive systematic literature review which has resulted in an analysis of 90 relevant articles out of a total of 104 articles from a period of 1978–2019. The review reveals no consensus on a standardized framework to synergize the already available strategies and methodologies for improving Nigeria's energy access. An integrated framework that embodies a multi-disciplinary study is introduced and forms the foundation upon which the authors of this paper are conducting further research to conceptualize a unified road map for energy planning, system design, and operation with renewable energy integration geared towards improving localized energy access in Nigeria. Highlights: State of the art on Nigerian energy access studies. Universal building blocks for future energy access studies. A novel Integrated framework for energy access studies. A unified road map for streamlining future research activities and endeavours.